THE ROLE OF THE EDUCATOR IN SHAPING THE CHARACTER OF PRESCHOOL-AGED CHILDREN (Modern education and development, 2025)
This article explores the significant role that preschool educators play in the moral, emotional, and social development of children aged 3 to 6. At this formative stage, children are highly impressionable, and the educator acts not only as a teacher but also as a role model, emotional guide, and moral leader. Through structured routines, consistent behavior, and emotionally supportive interaction, educators influence how children learn values such as empathy, honesty, patience, and cooperation. The study is based on classroom observations, teacher interviews, and curriculum analysis, revealing that educators who intentionally model prosocial behavior and incorporate moral lessons into everyday activities have a lasting impact on children’s character development.